A homiletic credo – A firm belief in the preaching event - Müller, Bethel (Nederduitse Gereformeerde Teologiese Tydskrif, 2013)
From 1981 to 2002 the author, together with Dirkie Smit and Coenie Burger were responsible for the publication of 22 volumes of Sermon Helps, which embodied a specific theological and homiletical approach to the preaching event. The author finds it remarkable that after 30 years these homiletical premisses are still adhered to in what he describes as his homiletical credo regarding the preaching event (event here as translation of what leading German homileticians describe as a “Wortgeschehen”. He concentrates on this event as an encounter between listening to the living voice of God in the text and its modern context. This is in essence a hermeneutical encounter, striving to incarnate the Living Word in the language of the day, taking the text “into the night” of hard exegetical labour – and all consuming prayer. Thereby the preaching event issues in joyous celebration of the glory of God.